2008
DOI: 10.1016/j.nucmedbio.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of vesicular monoamine transporter 2 in pancreas using an 18F epoxide derivative of tetrabenazine

Abstract: Objectives-Development of imaging agents for pancreatic beta cell mass may provide tools for studying insulin-secreting beta cells and their relationship with diabetes mellitus. In this paper a new imaging agent, [ 18 F](+)-2-oxiranyl-3-isobutyl-9-(3-fluoropropoxy)-10-methoxy-2,3,4,6,7,11b-hexahydro-1H-pyrido[2,1-a]isoquinoline [ 18 F](+)4, which displays properties targeting vesicular monoamine transporter 2 (VMAT2) binding sites of beta cells in the pancreas, was evaluated as a PET (positron emission tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Similar levels of pancreatic uptake of 3 H-DTBZ and 11 C-DTBZ as well as DTBZ derivatives were reported previously (13,14,22,23). In those studies, the islet and VMAT2 specificity of the accumulated radioactivity was not assessed directly.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar levels of pancreatic uptake of 3 H-DTBZ and 11 C-DTBZ as well as DTBZ derivatives were reported previously (13,14,22,23). In those studies, the islet and VMAT2 specificity of the accumulated radioactivity was not assessed directly.…”
Section: Discussionsupporting
confidence: 76%
“…A higher affinity for VMAT2 could improve the labeling of pancreatic islets. However, because 11 C-DTBZ and its derivatives displayed similarly high levels of pancreatic uptake when injected into rats (22,23), the derivatives are likely to exhibit the same type of nonspecific pancreatic binding as the parent compound.…”
mentioning
confidence: 99%
“…Strategies for imaging BCM by positron emission tomography (PET) and single photon emission tomography (SPECT) using radiotracers targeted to β-cell-specific binding sites have been explored (19). Of the radioligands identified to date, only those targeting vesicular monoamine transporter type 2 (VMAT2) have warranted phase 1 clinical evaluation for quantitative imaging of BCM in humans (59). …”
mentioning
confidence: 99%
“…11 C-dihydrotetrabenazine, a PET tracer that had been developed to visualize VMAT2 in the brain (6), was applied in PET studies of diabetes and showed less pancreatic uptake in diabetic rats than in control rats (5) and a longitudinal decrease in the pancreatic standardized uptake value (#65%) of spontaneous diabetic rats (7). Encouraged by these results, researchers have synthesized and are evaluating several 18 F derivatives of dihydrotetrabenazine (8,9).…”
Section: See Page 1439mentioning
confidence: 99%